Ombres et transparences, de Vinci aux calques numériques - Marie-Madeleine Martinet (Sillages Critiques)
Shadows, which are a form of imitation, combine contiguity and similarity. Sfumato as recommended by Leonardo, shadows ‘explaining’ objects according to Hogarth, entail contextualisation; they imply partial transparency, still required in digital image settings. Optical devices have since the Renaissance superimposed shadow and transparency; they have evolved from image-making to the continuous representation of motion in 19th-century toys based on the rotation of silhouettes; copying machines, derived from ancient legends defining shadows as the image of persons, led to 18th-century experiments in the simulation of motion. Studies of reflexion ranged from mirror-images to sets of multiple contiguous spots of light; form/texture relationships changed over the centuries from the gradual recomposition of motifs – as in multiple-colour printing– to decomposition –as in camouflage. In the theme of windows within paintings, transparency shifted from analogous infinite regress effect to contextualisation; 20th-century models of geometrical forms suppressed the interior-exterior distinction as they became glass volumes.